Indications for ultra-high pressure metamorphism of amphibolite xenolith in the Arnea granite - ΙΩΑΝΝΙΔΗΣ, Ν.; ΣΚΛΑΒΟΥΝΟΣ, Σ. (Bulletin of the Geological Society of Greece, 2001)
In this paper an amphibolite rock presented as xenolith into the Arnea granite close to Marathousa village has been examined. In particular, the xenolith is exposed into the aplitic granite portion of the Arnea granite at its contact with the Serbomacedonian massif. Microscopic studies and chemical analyses carried out in samples from the amphibolite xenolith and its contact zone with the aplitic granite has indicated the existence of tetrahedral and octahedral forms of "graphitized diamonds". This denotes that the amphibolite xenolith is the retrograde metamorphic rock of a previously, possibly eclogite rock, which the later was metamorphosed at least under ultra-high pressure metamorphic conditions. Mineral parageneses of the xenolith, as well as the use of the geobarothermometric methods have shown that the xenolith has been subjected to at least three metamorphic events. The first was attributed to a ultra-high pressure of at least 30-35kb, the second to a P-T conditions corresponding to 15kb and about 670 °C and the latest to 8.4 ± 1,2 kb and 380 ± 34 °C. The latest greenschist metamorphic event is the only metamorphic one imprinted in the Arnea granite. Taking account the latest dating of the Arnea granite crystallization age in Late Triassic (215 ± 1,8 Ma), we suggest that the examined xenolith was probably a part of a sedimentary crustal rock that metamorphosed to ultra-high pressure conditions associated with a deep subduction zone in the Late Paleozoic times. During Triassic it was retrograde metamorphosed to the amphibolitic metamorphic phase probably associated with a general uplifting of the area and finally it ascended as xenolith along with the Arnea granite to more shallow depths where they both subjected to the greenschist metamorphic event.